Immune reconstitution after allogeneic hematopoietic stem cell transplantation in children: a single institution study of 59 patients - Hyun O Kim; Hyun Jin Oh; Jae Wook Lee; Pil-Sang Jang; Nack-Gyun Chung; Bin Cho; Hack-Ki Kim (Korean Pediatric Society, 2013)
PurposeLymphocyte subset recovery is an important factor that determines the success of hematopoietic stem cell transplantation (HSCT). Temporal differences in the recovery of lymphocyte subsets and the factors influencing this recovery are important variables that affect a patient's post-transplant immune reconstitution, and therefore require investigation.MethodsThe time taken to achieve lymphocyte subset recovery and the factors influencing this recovery were investigated in 59 children who had undergone HSCT at the Department of Pediatrics, The Catholic University of Korea Seoul St. Mary's Hospital, and who had an uneventful follow-up period of at least 1 year. Analyses were carried out at 3 and 12 months post-transplant. An additional study was performed 1 month post-transplant to evaluate natural killer (NK) cell recovery. The impact of pre- and post-transplant variables, including diagnosis of Epstein-Barr virus (EBV) DNAemia posttransplant, on lymphocyte recovery was evaluated.ResultsThe lymphocyte subsets recovered in the following order: NK cells, cytotoxic T cells, B cells, and helper T cells. At 1 month post-transplant, acute graft-versus-host disease was found to contribute significantly to the delay of CD16+/56+ cell recovery. Younger patients showed delayed recovery of both CD3+/CD8+ and CD19+ cells. EBV DNAemia had a deleterious impact on the recovery of both CD3+ and CD3+/CD4+ lymphocytes at 1 year post-transplant.ConclusionIn our pediatric allogeneic HSCT cohort, helper T cells were the last subset to recover. Younger age and EBV DNAemia had a negative impact on the post-transplant recovery of T cells and B cells.